2020
DOI: 10.1016/j.jvir.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Malignant Superior Vena Cava Syndrome through Upper-Limb Access: A Comparison between Venous-Dedicated and Conventional Stents

Abstract: Purpose: To retrospectively evaluate the technical and clinical outcomes of superior vena cava (SVC) stent placement through upperlimb venous access in malignant SVC syndrome (SVCS) and compare the efficacy of different nitinol stent types. Materials and Methods: Between 2006 and 2018, 156 patients (132 male; mean age, 62 y; age range, 33-81 y) underwent SVC stent placement for malignant obstructions through upper-limb venous access with 1 of 3 types of nitinol stent: 1 venous-dedicated (Sinus-XL stent) and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…A study by Matthaiou et al demonstrated no significant difference in primary patency rates for venous and non-venous-dedicated stents in the setting of malignant SVC syndrome in 156 patients. 16 However, there is currently limited clinical outcome data supporting the specific use of the Abre TM stent for SVC syndrome. Few studies have reported clinical improvement in the management of central venous occlusion in hemodialysis patients using the Abre TM stent, 9 while studies reporting use of the Abre TM for SVC syndrome have limited clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Matthaiou et al demonstrated no significant difference in primary patency rates for venous and non-venous-dedicated stents in the setting of malignant SVC syndrome in 156 patients. 16 However, there is currently limited clinical outcome data supporting the specific use of the Abre TM stent for SVC syndrome. Few studies have reported clinical improvement in the management of central venous occlusion in hemodialysis patients using the Abre TM stent, 9 while studies reporting use of the Abre TM for SVC syndrome have limited clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%